PENGARUH SUHU CURING BETON TERHADAP KUAT TEKAN BETON - Mooy, Merzy; Simatupang, Partogi H.; Frans, John H. (Jurnal Teknik Sipil, 2017)
Concrete is mostly used in the world of construction due to cheap price and easy implementation. However extensive knowledge is required about the quality of basic materials, ways of making, curingto increase concrete function to be more leverage.The purpose of this study is to know about the effect of curing temperature to concrete compressive strengthand which one of curing temperature that produce the optimal compressive strength, compressive strength by elevated temperature curing time 28 days that projected by long cycle steam curing method and maturity method, also the compressive strength rate ratio by normal curing temperature, low and elevated curing temperature.Based on the calculation of the results obtainedthe effect of curing temperature to average concrete compressive strength by normal curing temperature 29 °C is 23,85 MPa, low curing temperature -10 °C is 26,29 MPa, and elevated curing temperature in the oven 87,5 °C is 31,80 MPa so that the most optimal concrete compressive strength is by elevated curing temperature. The concrete compressive strength that projected by long cycle steam curing method and maturity method is 27,06 MPa. The compressive strength rate ratio by normal, low and elevated curing temperature is 0,85 : 0,94 : 1,14